New strategies of insulin therapy - a way to effective glycemic control of type 2 diabetes mellitus - Elena Valer'evna Biryukova (Сахарный диабет)
This paper focuses on the approaches to target glycemic control in patients with type 2 diabetes mellitus. It is emphasized that timely onset of insulintherapy enhances glycemic control and reduces the risk of vascular complications. One way to achieve this goal is to use modern strategies of intensivehypoglycemic therapy with insulins having improved pharmacokinetic and pharmakodynamic properties, e.g. glargine (Lantus) and glulysine (Apidra).Results of international clinical studies confirm effi-ciency of basal and basal-plus insulin strategies allowing to achieve glycemic control in type 2diabetes without heightening the risk of hypoglycemia, development and progression of vascular complications.